Relooking the curriculum and assessment in undergraduate pathology - Yookarin Khonglah; Vandana Raphael; Jaya Mishra; Evarisalin Marbaniang; Zachariah Chowdhury; Biswajit Dey (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Pathology is basic science, and steps are being taken to integrate the clinical sciences in undergraduate pathology curriculum. The present study was undertaken with the aim to assess the need for revision of the undergraduate pathology curriculum with a focus on assessment methods. MATERIALS AND METHODS: This study included a questionnaire-based, anonymous, survey in a 5-point Likert-type scale for undergraduate students who have completed pathology subject including the interns and a qualitative approach through interviews and focus group discussions from the pathology senior residents and faculties using the essentialist thematic analysis. RESULTS: There were a total of 109 feedbacks from undergraduate students and also the interns. A total of 10 feedbacks from the senior residents and faculties were analyzed. About 70%-90% of the students were satisfied with the pathology curriculum and teaching and clinical integration in pathology. However, only 52.3% of students felt morphology being extremely important as compared to 80% of faculties, showing a discrepancy between the students' perception of the importance of morphology and that of the faculties. CONCLUSION: Although both students and faculties find the curriculum adequate, it is suggested that teaching could be made more clinical oriented. The assessment based on morphology should be given less emphasis during the assessment.